Influence of Paratuberculosis Vaccination on the Local Immune Response in Experimentally Infected Calves: An Immunohistochemical Analysis - David Zapico; José Espinosa; María Muñoz; Luis Ernesto Reyes; Julio Benavides; Juan Francisco García Marín; Miguel Fernández (Animals)
Vaccination remains the most cost-effective way to control clinical paratuberculosis in dairy herds, but its effect on the immune response at the intestine have been poorly characterized. The aim of this study was to evaluate the expression of toll-like receptor (TLR)-1, TLR2, TLR4, TLR9, interferon (IFN)-γ, inducible nitric oxide synthase (iNOS) and cluster of differentiation (CD)-204 in calves vaccinated with Silirum® and then experimentally infected with paratuberculosis, using immunohistochemical techniques. Samples of the injection-site granuloma, scapular lymph node, intestine and mesenteric lymph nodes were studied. Lesions were classified as focal, multifocal and diffuse paucibacillary (lymphocytic). The immunolabeling for TLR1, TLR2, TLR4 and IFN-γ was assessed according to the number of immunolabeled cells, while TLR9, iNOS and CD204 immunolabeling in the lesions was evaluated using a histological score (H-score). Vaccinated calves with focal forms showed a significant increase in the number of macrophages immunolabeled TLR2 at the intestine and in the H-score values for iNOS in the granulomas. A greater immunolabeling of TLR2 and IFN-γ was detected at the injection-site granuloma. Animals with multifocal lesions, regardless of the vaccination status, showed lower numbers of TLR2+ macrophages and higher H-score values for CD204 in the granulomas. Thus, the protection conferred by the Silirum® vaccine is associated with an enhanced immunological response in the intestine.